Open Research Data in Biomedicine: A Step Forward in Defining an Italian National Policy - Poltronieri, Elisabetta; Curti, Moreno; De Castro, Paola; Ferrara, Rosalia; La Placa, Pietro; Mancini, Cristina; Toni, Franco; Vullo, Angela (Qualitative and Quantitative Methods in Libraries; Vol 8 No 3 (2019): September 2019 Issue, 2019)
The concept of openness to research output has been strengthened by the current EU funding research programme Horizon 2020. In early 2017 the BISA (Bibliosan for Open Science) inter-institutional Working Group, including scientific information experts mainly from Istituto Superiore di Sanità (ISS, Italian National Institute of Health), carried out a survey on the practical handling of research data produced by Bibliosan affiliated institutions, the Italian Biomedical Research Libraries Network promoted by the Italian Ministry of Health. The BISA online questionnaire collected over 2,400 responses obtained from 58 Bibliosan institutions. Among the various aspects of data management covered by the BISA questionnaire, that one referring to the need of a policy and guidelines, to be adopted by Bibliosan research institutions, for dealing with research data was deeply investigated.